Framework of Reference for Chinese Language - T. L. Guruleva (Высшее образование в России)
The key theme of the article is the study of the competence of the framework of reference for Chinese language. The history of the development of the framework of reference for Chinese language in the PRC is briefly presented. The components of the communicative competence of the Chinese language and its level structure are studied. The author has performed a comparative analysis of the component structure and content of the components of the model of the communicative competence of the Chinese language with western, domestic and European models of communicative competence, as well as comparative analysis of the levels of the framework of reference for Chinese language with the levels of the Common European Framework of Reference for Languages. The conclusion is made about the specificity of the Chinese model of communicative competence, reflecting the features of the isolating Chinese language, the verbal syllabic Chinese hieroglyphic writing, the autochthonous Chinese culture, and the related features of teaching Chinese as a foreign language.